A three-choice minority game-based mechanism design for the utilization of a capacity-constrained resource - Montes, Catalina; Valdez, Adrian Roy L.; Festin, Susan P. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
As new technologies emerge, challenges in solving resource allocation problems continue to manifest themselves. An example of this is in the renewed interest in developing demand response models for emerging energy grid paradigms such as microgrids. In tackling general resource allocation challenges, minority games have been used as modeling tools. This thesis explores how a three-choice minority game model may be used to produce a mechanism design for general resource allocation, and its possible application as a demand response model. Two studies which utilize the proposed three-choice minority game are presented in this thesis. The first study aims to find agent distributions that equalize or maximize the social welfare. Meanwhile, the second work examines how cost functions can influence agent decisions so that a desired capacity of agents per choice is attained. The first study's results show that ideal agent distributions are computable, under the assumptions taken. Similarly, the second study's results show that costing schemes can influence agent behavior to meet desired capacities per choice. These results indicate promising applications of the three-choices minority game as a demand response model. The second work thus concludes with proposed possible applications of the game system for modeling demand response.
Thesis (Master of Science in Computer Science)--University of the Philippines Diliman
Keywords: Resource allocation; Game theory